ANALISIS KINERJA KEPALA SEKOLAH TK DALAM BIDANG SUPERVISI SE-KECAMATAN TAMPAN KOTA PEKANBARU - Luluk Aniqiyah; Wilson Wilson; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstarck: There are some phenomena that is happening in supervision of field activities focused on the administration, the headmaster doing supervision about performance of teacher to promotion, supervision doing in six months, headmaster rarely visit and monitor the performance of teachers in learning activities in the classroom , as well as the headmaster rare to guide the teacher in the learning performance. The purpose of this study was to determine the performance of kindergarten headmaster in the areas of supervision In Tampan sub-Districk Pekanbaru. The population and sample of this research is all kindergarten headmaster of 48 people. The technique of data analysis using the percentage formula. The results were obtained kindergarten headmaster’s performance in the areas of supervision In Tampan sub-Districk Pekanbaru overall percentage of 71.70% was obtained sufficient criteria. Where as when viewed from each indicator, the indicator planning supervision program obtained a percentage of 69.49% which is the sufficient criteria, indicators carry out supervision obtained percentage of 73.22% which is the sufficient criteria and indicators to follow up the results obtained percentage supervision about to 71.47% at the sufficient criteria.Key Words: performance, supervisionWISUDA OKTOBER